Analisis Dampak Ukuran Perusahaan dan Manajemen Laba terhadap Tanggung Jawab Sosial Perusahaan pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia - Sitti Zahra Zahraeny; Jumriani Jumriani; Yelsa Yelsa (AKUNTANSI 45, 2026)
This study aims to analyze and examine the effect of company size and earnings management on corporate social responsibility (CSR) in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX). The research data were obtained from annual financial reports accessed through www.idx.co.id, using a purposive sampling technique, resulting in 57 companies as samples out of 159 population. Data analysis was performed using multiple linear regression with SPSS version 26. The results show that company size has a significant negative effect on CSR disclosure, while earnings management has no significant effect on CSR. These findings indicate that large-scale companies do not necessarily have higher CSR disclosure levels, as many have yet to fully adopt the comprehensive Global Reporting Initiative (GRI) G-4 standards. Meanwhile, earnings management activities carried out by companies do not directly contribute to increasing CSR practices. This study is expected to provide insights for company management, investors, and policymakers to enhance transparency and corporate social accountability in Indonesia.